"I Will Have Lacked": Rethinking Sexual Difference and Sexed Subjectivity Through Psychoanalytic Temporal Relationality. Issue 1 (2nd January 2020) - Wang, Chenyang
ABSTRACT: Sexual difference, as understood by contemporary Lacanian scholars, is the Real that marks a constitutive gap or discord beneath the construction of sexual identity, but in what way does the Real relate to the Symbolic in a process of becoming a sexed subject? This article explores the possibility of sexual differentiation through a psychoanalytic conceptualization of temporal organization and rearrangement. Taking the moment of the "primal view" in Freud's text as its point of departure, this article demonstrates that the origin of sexual difference in psychoanalysis is actually a temporal difference between two processes of becoming, explained by Freud's Nachträglichkeit and Lacan's future anterior, respectively. In comparison with women's time, it is argued that the Lacanian temporal relationality promotes a new epistemology of sexed subjectivity that permits an expanded understanding of the lived experience of being sexed.